SPARK : How to Lead Yourself and Others to Greater Success - Morgan, Angie; Lynch, Courtney; Lynch, Sean (NEW YORK : Mariner Books Houghton Mifflin Harcourt, 2018)
Pinpointing leaders is not an easy task. All managers know that within their organization there are certain key employees who are "sparks"-those rare individuals who have a natural drive not only to get the job done, but to go far beyond what is called for. These special employees truly get more accomplished in a day than others can in a week or more. These "sparks" are the unique and essential people in your workplace who can help transform your company in all sorts of magical ways. And it's your job to find them, empower them, and enable them to become the true leaders they are destined to be. Based on hard-earned insights and case studies gleaned from their military experience as well as corporate leadership training, Angie Morgan (U.S. Marine Corps), Courtney Lynch (U.S. Marine Corps), and Sean Lynch (U.S. Air Force) reveal how you can pinpoint the sparks within your ranks, and how you can unleash them to take your company to the next level.
Includes index
Keywords: Leadership; Motivation (Psychology)